2014
DOI: 10.1007/s00404-014-3386-2
|View full text |Cite
|
Sign up to set email alerts
|

The significance of fetal inflammatory response syndrome in early and later adaptation of premature infants

Abstract: The correlation between the concentration of the inflammatory markers IL-6 and tTNF-α in umbilical cord blood at 22-34 weeks of gestation and acute RDS, and the death of preterms was determined. Significant values of umbilical cord blood IL-6 and tTNF-α concentration for predicting the lethal outcome in the later adaptation of preterms were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Recent studies have demonstrated a correlation between the development of severe RDS and umbilical cord blood IL‐6 concentration . Likewise, in the present study, among the FIRS group, umbilical cord blood IL‐6 concentration of premature infants with RDS was found to be higher than that in infants without RDS.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Recent studies have demonstrated a correlation between the development of severe RDS and umbilical cord blood IL‐6 concentration . Likewise, in the present study, among the FIRS group, umbilical cord blood IL‐6 concentration of premature infants with RDS was found to be higher than that in infants without RDS.…”
Section: Discussionsupporting
confidence: 77%
“…and Hofer et al. , a correlation was found between inflammatory biomarkers and neonatal death . Pilpiene et al .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…25 Moreover, it was associated with adverse neonatal outcomes including intraventricuar hemorrhage, early-onset sepsis, bronchopulmonary dysplasia, death, and RDS. 26,27 In our study, 12,450/mm3 is the cutoff point to predict BA (AUC 0.68, 95%CI 0.57-0.80, Sensitivity 46.7%, Specificity 88%). In addition, Gibbs, et al found 15,750/mm 3 as significant mean level correlated with intraamniotic infection.…”
Section: Discussionmentioning
confidence: 48%